Life cycles of Eukiefferiella claripennis (Lundbeck 1898) and Eukiefferiella minor (Edwards 1929) (Diptera: Chironomidae) in spring-fed streams of different temperatures with reference to climate change - Elísabet Ragna Hannesdóttir; Gísli Már Gíslason; Jón S Ólafsson (Fauna Norvegica, 2012)
The effect of temperature on the life cycles of two chironomid species, Eukiefferiella claripennis and Eukiefferiella minor, was studied by comparing populations from seven spring-fed streams, ranging in annual average temperatures between 5.4°C and 21.3°C. Dependent on stream, both species showed differences in their life cycles: E. claripennis was regarded univoltine in the two coldest streams, IS7 (annual average 5.4°C) and IS11 (5.3°C), and bivoltine or multivoltine in the warmer streams (ranging from 9.7°C to 21.3°C). E. claripennis developed and grew slower in the colder streams compared to the warmer ones. The winter generation in the warmer streams took longer time to complete compared to the summer generation. E. minor was bivoltine in all the streams, with no emergence during the winter in the colder streams, but in one of the warmer streams (IS6, 13.3°C) emergence was continuous throughout the year. In four streams (IS7, cold; IS6, IS5 and IS1, warm) E. minor may even have been multivoltine. There was no trend between the number of generations completed in one year and stream temperature for E. minor. The summer generation of E. minor in the cold stream IS7 produced smaller larvae compared to the winter generation. Following global warming the life cycle of E. claripennis is expected to change from univoltine to bivoltine, and could show changes in emergence pattern. E. minor on the other hand, will likely show less change in its life cycle. Changes in emergence pattern of E. minor could though be possible.